PERSEPSI REMAJA USIA 15-24 TAHUN TERHADAP KONTEN NEGATIF SETELAH MENONTON CHANNEL YOUTUBE WINDAH BASUDARA - marta yansi, kenanga (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Abstract: This study aims to understand how teenagers respond to the Windah Basudara Youtube Channel which belongs to a Youtuber Gaming who uses harsh words and gimmicks (drama) to attract the attention of the audience. The purpose of this research is to understand the youth's perception of the channel and the factors that influence their perception of content of the Windah Basudara Youtube Channel. This study uses a qualitative approach and descriptive research type. The focus of research is a scientific subject which includes behavior, perception, motivation, and action. This research is based on the theory of perception theory and involves interviews with informants to obtain an overview of the views of the respondents, and the conclusions on the research are based on the responses given by the informants. Windah Basudara is a fun gaming Youtuber and sometimes does charity work. Windah actively listens to her audience despite suggestions that are not true. The majority of the audience displayed positive behavior, although there were some negative ones. Content creators like Windah can be a motivation to make changes, even in small ways. They find content entertaining, motivating, and invite them to share in charity content. The content is invaluable for Youtubers beginner and those who want to start in the world of Youtube. Windah has a frontal and toxic style of speaking that attracts the interest of the millennial generation. He is also known as the "Ayah Kematian". Keywords: Perception. Youtube, Social Media, Perseption Theory.